Kolaborasi pentahelix dalam konservasi ex-situ berbasis pemberdayaan masyarakat - Mohammad Hikam Rofiqi; Setianingsih dwi (Dimensia: Jurnal Kajian Sosiologi, 2026)
Ex-situ conservation is the management of biological resources outside their natural habitats to ensure sustainability and maintain biodiversity. This qualitative case study at UD. Gentan Farm, Ponorogo, used observation, interviews, and documentation with purposive sampling. Analyzed through Talcott Parsons’ AGIL theory, the study highlights the importance of synergy among the five pentahelix elements for effective conservation. Results show that community empowerment, technical training, and regulatory support enhance the sustainability of green peacock conservation. Despite challenges like limited resources and low participation, these can be addressed through effective communication and shared goals. The program has led to ecosystem restoration, biodiversity preservation, cultural protection, and community development.